The controlling nutritional status score as a predictor of survival in hematological malignancies: a systematic review and meta-analysis - Lu, Guimei; Li, Qingqing (Frontiers in Nutrition, 2024)
The controlling nutritional status score (CONUT) has been widely used for ascertaining the prognosis of various cancers. However, its utility in patients with hematological malignancies is unclear. This review examined evidence on the utility of CONUT as a prognostic marker for patients with hematological malignancies.All cohort studies examining the association between CONUT and outcomes of hematological malignancies and published on the databases of Embase, Scopus, CENTRAL, Web of Science, and PubMed were searched up to 30 th January 2024. The primary outcome was overall survival (OS) and the secondary outcome was progression-free survival (PFS).Results: 23 studies were available for review. Meta-analysis of 22 studies showed that high CONUT was significantly associated with poor OS in patients with hematological malignancies (HR: 1.95 95% CI: 1.62, 2.35 I 2 =89%). Results remained unchanged on sensitivity analysis and subgroup analysis based on study location, sample size, diagnosis, CONUT cut-off, and Newcastle Ottawa Scale score. Just six studies reported data on PFS and pooled analysis found that high CONUT was a significant marker for poor PFS in patients with hematological malignancies (HR: 1.64 95% CI: 1.21, 2.20 I 2 =70%). These results too maintained significance in sensitivity analysis.CONUT is an independent predictor of poor OS in patients with hematological malignancies. The results seem to be valid across different cancer types and with different CONUT cut-offs. Scarce data also suggests that CONUT could predict PFS.